1998
DOI: 10.1105/tpc.10.12.2103
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Activation of Jasmonate and Ethylene Response Pathways Is Required for Induction of a Plant Defensin Gene in Arabidopsis

Abstract: Activation of the plant defensin gene PDF1.2 in Arabidopsis by pathogens has been shown previously to be blocked in the ethylene response mutant ein2-1 and the jasmonate response mutant coi1-1. In this work, we have further investigated the interactions between the ethylene and jasmonate signal pathways for the induction of this defense response. Inoculation of wild-type Arabidopsis plants with the fungus Alternaria brassicicola led to a marked increase in production of jasmonic acid, and this response was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
435
2
15

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 937 publications
(469 citation statements)
references
References 43 publications
17
435
2
15
Order By: Relevance
“…Expression levels of the SA pathway marker genes PR1, PR2, and PR5 and the JA/ET signaling marker genes PLANT DEFENSIN1.2 (PDF1.2), PR4, and BASIC CHITINASE (ChiB) in the samples were examined by real-time quantitative PCR. [5][6][7][8] Confirming the previous results, 1 NADP addition significantly induced the SA pathway marker genes (Fig. 1A).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Expression levels of the SA pathway marker genes PR1, PR2, and PR5 and the JA/ET signaling marker genes PLANT DEFENSIN1.2 (PDF1.2), PR4, and BASIC CHITINASE (ChiB) in the samples were examined by real-time quantitative PCR. [5][6][7][8] Confirming the previous results, 1 NADP addition significantly induced the SA pathway marker genes (Fig. 1A).…”
supporting
confidence: 90%
“…1B). A time course experiment confirmed that PDF1.2 was not induced at several times (8,16, and 24 hr) when the PR1 gene was significanty activated (Fig. 1C).…”
mentioning
confidence: 52%
“…The methoxyflavone tricin acts as an antifeedant in Poaceae (Simmonds 2003), and phenolic compounds, such as quercetin or caffeic acid, are highly effective antioxidants in response to UV irradiation. Jasmonate (JA) and ethylene are considered to be critical signal molecules in wounding signal transduction that simultaneously or individually trigger an increase in the expression of defense-related genes (Penninckx et al 1998). Therefore, the wound-inducible TaOMT1 gene might be coordinately regulated by JA and ethylene.…”
Section: Structure and Sequence Comparison Of The Taomt Genesmentioning
confidence: 99%
“…JA and ethylene can be either synergistic or antagonistic hormones in terms of the expression of defensive genes in response to insect attack [5] [6] [7] [8], while both of these hormones mediate against pathogen attack (partly by defense gene induction) [9]. Curiously, plants deficient in ethylene signaling show either increased susceptibility or increased resistance, depending on the plant and pathogen [10].…”
Section: Introductionmentioning
confidence: 99%